Hubungan Antara Faktor Kepribadian Big Five Dengan Perilaku Prososial Pada Mahasiswa Keperawatan - Retno Wisudiani (2012)
The study aimed to determine whether there was a correlation between The Big Five Factor Personality and the prosocial behavior among nursing students. This study was held in Airlangga University Faculty of Nursing with the students as the subject. The subject consists of 11 men and 73 women adding up to 84 students in total. For data collector tool, prosocial behaviour scale was used with Likert pattern consisting of 50 items and Big Five scale for measuring personality factor which was a modification of Big Five-100 items scale compiled by Goldberg into 88 items. Data analysis performed using Spearman's Rho correlation technique with the help of SPSS version 16.0 for Windows. The correlation value between extraversion factor and prosocial among nursing students obtained from data analysis, was 0,041 with p < 0,05. This showed that there was a correlation between extraversion and prosocial among nursing students. The correlation value between agreeableness factor and prosocial was 0,000 with p < 0,05, which meant that there was a correlation between agreeableness and prosocial among nursing students. The correlation value between conscientiousness factor and prosocial was 0,000 with p < 0,05, which meant that there was a correlation between conscientiousness and prosocial among nursing students. The correlation value between neuroticism factor and prosocial was 0,036 with p < 0,05, which meant that there was a correlation between neuroticism and prosocial among nursing students. The correlation value between openness factor and prosocial was 0,002 with p < 0,05, which meant that there was a correlation between openness and prosocial among nursing students.